Однофакторне прогнозування фінансових ресурсів Збройних сил України в умовах прагнення України до стандартів НАТО - Чистик, О.М. (Економіко-математичне моделювання соціально-економічних систем, 2016)
The article attempts to build optimistic and pessimistic forecasts expenditures for defense of Ukraine till 2020. Done model trend growth in defense spending for the period until 2020.